Interactions in the microbial community of the marginal ice zone of the northwestern Weddell Sea through size distribution analysis - Becquevort, Sylvie; Mathot, Sylvie; Lancelot, Christiane (1992)
Enumeration and identification of planktonic microorganisms (phytoplankton, bacteria, protozoa) were carried out for 16 stations sampled in the marginal ice zone of the northwestern Weddell Sea during sea-ice retreat in 1988 (EPOS Leg 2). From these data, carbon biomass distribution among various classes, chosen according to size and trophic mode, has been determined. This analysis reveals the general dominance of nano-phytoplankton (74 %), mainly Cryptomonas sp. In two stations only, significant microphytoplanktonic biomass occurred. Bacterioplankton biomass was 16 % of the phytoplanktonic biomass. Protozooplankton appeared as a significant group whose biomass represented an average of 23 % of the total microbial biomass. Maximum phytoplankton and protozooplankton biomass was reached at about 100-150 km north of the receding ice edge whilst bacteria did not show marked spatial variations. From these results, indirect evidence for close relationships between protozoa and bacteria, as well as protozoa and autotrophs, is given. The size range of autotrophic prey and predators overlaps (equivalent spherical diameter range = 6 to 11 μm). This size overlapping increases the complexity of the trophic organization of the microbial community. Our results thus support the idea of a flux of energy not always oriented towards an increasing particle size range. Potential ingestion rate, calculated from a mean clearance rate in the literature, indicated that protozooplankton might ingest as high as 48 % of the daily phytoplankton production in the marginal ice zone. © 1992 Springer-Verlag. info:eu-repo/semantics/published